Physician specialization and antiretroviral therapy for HIV. - Landon, Bruce E; Wilson, Ira B; Cohn, Susan E; Fichtenbaum, Carl J; Wong, Mitchell D; Wenger, Neil S; Bozzette, Samuel A; Shapiro, Martin F; Cleary, Paul D (Journal of general internal medicine, 2003)
Since the introduction of the first protease inhibitor in January 1996, there has been a dramatic change in the treatment of persons infected with HIV. The changing nature of HIV care has important implications for the types of physicians that can best care for patients with HIV infection.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Clinical Competence; Cohort Studies; Education, Medical; Female; HIV Infections; Humans; Male; Medicine; Middle Aged; Multivariate Analysis; Physician's Practice Patterns; Primary Health Care; Quality Assurance, Health Care; Questionnaires; Referral and Consultation; Specialization; Time Factors; United States